Organic viticulture elements development - Klimenko, O E; Klimenko, N I; Klimenko, N N (IOP conference series. Earth and environmental science, 2021)
The results of a two-factor field experiment on the application of two elements of organic planting: sowing of inter-row spacing and introduction of biofertilizers - microbial preparations for increasing soil fertility, growth and productivity of grapes (Vitis vinifera L.) of Chardonnay cultivar on rootstock cultivar Berlandieri x Riparia Kober 5BB (Kober 5BB) are presented. Study was carried out in 2016-2018. The intercropping factor has two options: natural overgrowing (NO) and sowing a mixture of grasses (MG) - pasture ryegrass (Lolium perenne L.), alfalfa (Medicago sativa L.) and meadow bluegrass (Poa pratensis L.) in a ratio of 1:1:1. For the factor microbial preparations (MP): Diazofit - Agrobacterium radiobacter 204 strain, associative nitrogen-fixer, and a complex of microbial preparations (CMP). It has been established that use of organic methods positively influenced the growth, productivity and quality of Chardonnay grapes in the foothill zone of the Crimea. MP provided the most significant effect on these indicators against the intercropping with a mixture of grasses. The applied methods of biologization contributed to an increase in the sugar content of the grapes, to a greater extent the MP and reduced the acidity of the berries juice, where intercropping played a significant role. The increasing in soil fertility under the vineyard with the application of intercropping and MP on its background has been revealed. Model of Chardonnay variety productivity on rootstock cultivar Kober 5BB in the conditions of the foothill Crimea by organic viticulture methods was constructed.